Direct interaction of kindlin-3 with integrin αIIbβ3 in platelets is required for supporting arterial thrombosis in mice - Xu, Zhen (2014)
OBJECTIVE: Kindlin-3 is a critical supporter of integrin function in platelets. Lack of expression of kindlin-3 protein in patients impairs integrin αIIbβ3-mediated platelet aggregation. Although kindlin-3 has been categorized as an integrin-binding partner, the functional significance of the direct interaction of kindlin-3 with integrin αIIbβ3 in platelets has not been established. Here, we evaluated the significance of the binding of kindlin-3 to integrin αIIbβ3 in platelets in supporting integrin αIIbβ3-mediated platelet functions. APPROACH AND RESULTS: We generated a strain of kindlin-3 knock-in (K3KI) mice that express a kindlin-3 mutant that carries an integrin-interaction defective substitution. K3KI mice could survive normally and express integrin αIIbβ3 on platelets similarly to their wild type counterparts. Functional analysis revealed that K3KI mice exhibited defective platelet function, including impaired integrin αIIbβ3 activation, suppressed platelet spreading and platelet aggregation, prolonged tail bleeding time, and absence of platelet-mediated clot retraction. In addition, whole blood drawn from K3KI mice showed resistance to in vitro thrombus formation and, as a consequence, K3KI mice were protected from in vivo arterial thrombosis. CONCLUSIONS: These observations demonstrate that the direct binding of kindlin-3 to integrin αIIbβ3 is involved in supporting integrin αIIbβ3 activation and integrin αIIbβ3-dependent responses of platelets and consequently contributes significantly to arterial thrombus formation